Recurrent Seizure: An Uncommon Presentation of Post Thyroidectomy Hypoparathyroidism (Journal of Medicine, 2015)
Basal ganglia calcification is associated with chronic hypoparathyroidism. We report a case of 37 year old lady with long standing iatrogenic hypoparathyroidism following total thyroidectomy. The clinical evaluation revealed neurological symptoms but without any neurological deficit. The CT scan of head showed calcification in caudate nucleus and part of lentiform nucleus of basal ganglia and in the cortical and subcortical white matter. Detection of brain calcinosis in patients who had total thyroidectomy can guide clinicians to further investigation for possible hypoparathyroidism.DOI: http://dx.doi.org/10.3329/jom.v16i1.22406 J MEDICINE 2015; 16 : 56-58